2020
DOI: 10.1002/tox.22947
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin ameliorates aluminum phosphide‐induced oxidative stress and mitochondrial damages in rat cardiomyocytes and isolated mitochondria

Abstract: Apart from the anticancer, antioxidant, anti‐inflammatory effects, and inhibition of aromatase, chrysin is involved in the protection of cardiovascular disorders. Cardiovascular complications are the main cause of death induced by aluminum phosphide (AlP) which is related to oxidative stress and mitochondrial damages. For this purpose, we investigated the effect of chrysin as an antioxidant and mitochondrial protective agent against AlP‐induced toxicity in isolated cardiomyocytes and mitochondria obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…The experimental groups were categorized into six groups in the current study. 1) In the control group, cardiomyocytes were treated with 0.05% DMSO for 3 h. 2) In the AlP group, cardiomyocytes were treated with 20 μg/ml of AlP (IC 50 3 h) for 3 h according to our previous study ( Khezri et al, 2020 ). 3) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 20 μM of Myr for 3 h. 4) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 40 μM of Myr for 3 h. 5) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 80 μM of Myr for 3 h. 6) In the Myr group, cardiomyocytes were treated with 80 μM of Myr for 3 h.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental groups were categorized into six groups in the current study. 1) In the control group, cardiomyocytes were treated with 0.05% DMSO for 3 h. 2) In the AlP group, cardiomyocytes were treated with 20 μg/ml of AlP (IC 50 3 h) for 3 h according to our previous study ( Khezri et al, 2020 ). 3) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 20 μM of Myr for 3 h. 4) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 40 μM of Myr for 3 h. 5) In the AlP + Myr group, cardiomyocytes were cotreated with 20 μg/ml of AlP and 80 μM of Myr for 3 h. 6) In the Myr group, cardiomyocytes were treated with 80 μM of Myr for 3 h.…”
Section: Methodsmentioning
confidence: 99%
“…The protective effect of chrysin on doxorubicin-induced cardiotoxicity is exerted via the mitochondrial apoptosis pathway and the inhibition of oxidative stress (Samarghandian et al, 2017). Similarly, Khezri et al found that treatment with chrysin significantly reduced the formation of ROS, lysosomal damage, mitochondrial damage and lipid peroxidation induced by ALP (Khezri et al, 2020). A recent study conducted by Jahedsani et al showed that apigenin also has the same protective effect as chrysin against ALP-induced myocardial damage (Mahajan et al, 2017).…”
Section: Insecticide-induced Cardiotoxicity Organophosphates-induced Cardiotoxicitymentioning
confidence: 97%
“…These questions have not yet been fully answered and require further investigation. For instance, aluminum is considered to be an inducer of the mitochondrial permeability transition [ 179 ], and aluminum phosphide can induce oxidative stress and mitochondrial damages in cardiomyocytes and isolated mitochondria [ 180 ]. Unfortunately, the transport of mitochondrial aluminum ions is still unclear.…”
Section: Other Mitochondrial Metal Ionsmentioning
confidence: 99%